The United States and the European Community (1969-1974): Economic and Political Disputes (Glocalism: Journal of Culture, Politics and Innovation, 2016)
This paper aims to examine the economic and political disputes between the United States and the European Community between 1969 and 1974. Utilising the documentary research approach, the paper will first explore the main economic disputes which were manifested in two rounds of the United States-European Community Consultation in 1970 and 1972. Then, it will investigate the divergence between the United States and the European Community in their policy stances on energy and the 1973 Arab-Israeli War which together constituted the major political disputes between the two sides. With these economic and political disputes, the years 1969-1974 witnessed a difficult phase of the United States-the European Community relations.
Keywords: United States; European Community; economic disputes; political disputes; oil crisis